Uncovering Reading Needs of Non-English Majors of Tribhuvan University - Pandey, Gopal Prasad (Nepal Journal of Multidisciplinary Research, 2020)
This study aimed at investigating into reading problems and needs of non-major English students of Tribhuvan University (TU), Nepal. Needs analysis (NA) plays an integral role in the process of designing and carrying out any language course, whether it is English for Specific Purposes (ESP) or general English course, and its centrality has been acknowledged by several scholars and authors. One hundred and two non-English majors and fifteen English teachers of Tribhuvan University participated in this study. Questionnaires served as the main tools for conducting an NA. The findings revealed that both the groups of participants perceived all seven sub-skills of reading as ‘important’. There is consistency between students’ perceptions of importance of subskills of reading and teachers’ perception of importance of the sub-skills. Regarding the perceived competence, teacher participants found their students’ abilities to be “not very good” or even “poor” in the subskills which they considered ‘important’ or ‘very important’. They rated their students at levels lower than the ones students did. The study also revealed that the students are poor at reading instruction booklets, company brochures and user manuals.